PENGARUH ENTREPRENEURIAL ECOSYSTEM TERHADAP ENTREPRENEURIAL INTENTION: PERAN MEDIASI ENTREPRENEURIAL SELF-EFFICACY DAN PERCEIVED BEHAVIORAL CONTROL PADA MAHASISWA SARJANA - Rahmat Dimas Darmawan; Fanny Martdianty (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2022)
Based on the Theory of Planned Behavior (TPB), this study aims to examine the influence of the entrepreneurial ecosystem on entrepreneurial intention, and to investigate the mediating role of entrepreneurial self-efficacy and perceived behavioral control in this relationship. This study used data collected from 426 undergraduate students from four different universities in the Greater Jakarta area. Through data processing carried out using the structural equation modeling (SEM) method, it was found that entrepreneurial self-efficacy and perceived behavioral control fully mediate the relationship between entrepreneurial ecosystem and entrepreneurial intention with no direct influence of entrepreneurial ecosystem on entrepreneurial intention. The increase in national entrepreneurship can be manifested through increasing the entrepreneurial intention on undergraduate students. The participation of various stakeholders, starting from the society, public media, educational institutions, and the government was found to play important roles in supporting its realization. This research is expected to enrich theoretical studies related to the influence of entrepreneurial ecosystems on entrepreneurial intentions of undergraduate students in developing countries context.Berlandaskan Theory of Planned Behavior (TPB), penelitian ini bertujuan untuk menguji pengaruh entrepreneurial ecosystem terhadap entrepreneurial intention, serta menginvestigasi peran mediasi entrepreneurial self-efficacy dan perceived behavioral control dalam hubungan tersebut. Penelitian ini menggunakan data yang dikumpulkan dari 426 mahasiswa sarjana yang berasal dari empat universitas yang berbeda di wilayah Jabodetabek. Melalui pengolahan data yang dilakukan dengan metode structural equation modelling (SEM) ditemukan bahwa entrepreneurial self-efficacy dan perceived behavioral control memediasi penuh hubungan antara entrepreneurial ecosystem dan entrepreneurial intention dengan tidak adanya pengaruh langsung entrepreneurial ecosystem terhadap entrepreneurial intention. Peningkatan wirausaha nasional dapat dimanifestasikan melalui peningkatan entrentrepreneurial intention mahasiswa sarjana. Partisipasi berbagai pihak pemangku kepentingan, dimulai dari masyarakat, media publik, lembaga pendidikan, hingga pemerintah ditemukan berperan penting untuk mendukung perwujudannya. Penelitian ini diharapkan dapat memperkaya kajian teoritis terkait pengaruh entrepreneurial ecosystem terhadap entrepreneurial intention mahasiswa sarjana dalam konteks negara berkembang.